Religion and Economic Development in History: Institutions and the Role of Religious Networks. Issue 1 (2nd January 2018) - Karaçuka, Mehmet
Abstract: I argue that the role of religion on economic performance is mainly through the networks of small religious groups. These groups form social networks that enable individuals to conduct non-formal contract enforcement mechanisms. I analyze the effects of religions on societies, focusing mainly on the institutional aspects that affect the capabilities of creating social capital via networks which enhance cooperation and decrease transaction costs. Since the interaction between institutions and organizations is expected to shape the institutional evolution and economic performance of an economy, religions that have a communal form of organization rather than a vertical (hierarchical) structure, thus allowing many different denominational sub-communities within a society, can be more beneficiary for development and growth. Such institutions may not only provide allocative and production efficiency, but also adaptive efficiency that is a key to long-run growth. However, these effects may turn negative depending on these institutions' role in causing group hostility and exclusion.